Previsibilidade da competividade empresarial: um estudo com indicadores de desempenho organizacional - Reckziegel, Valmor (2013)
Researchers in the field of strategy in their studies recognize that organizations are different reasons and influence internal and external, have different performance. The performance difference makes some companies more than others, and this phenomenon is defined in the field of research in business strategy for competitive advantage. Considering the wide debate on the subject, some authors mention the need to build a metric can predict the competitiveness and this search for indicators of competitive advantage has shown a lack of consensus among researchers in the field of strategy to define a construct capable of effectively predict the sustainability of the competitive advantage of organizations over time. Thus, this study aimed at validating the degree of competitiveness of a company, measured over a given period of time, an appropriate measure resulting from a combination of indicators, can provide competitive position for a period of several years in order to contribute with the theory of competitiveness construct a metric. Some studies, McGahan and Porter (1997), Wiggins and Ruefli (2002), Combs, Shook and Crook (2005), Brito and Brito (2012b), Santos and Brito (2012) and Brito, Chaddad and Lazzarini (2013) have contributed to filling this gap. This research is a quantitative, data were analyzed by the test of discriminant analysis in SPSS (Statistical Package for the Social Sciences), adopting the technique of exploratory factor analysis (varimax - principal components) to "save" of the linear regression factor single (creating score ranking of each company) for the period 1, classifying the companies into three groups (high, medium and low) and then applied to discriminant analysis with variable grading period 1 compared to group 2 variables . The sample companies were extracted from the database of economatica in 2005-2007 and 2010-2012, compared to ascertain the probability of predicting the competitiveness of enterprises in the second period based on competitive position in the first. The study results indicate that performance metrics, specifically profitability of equity combined with measures of growth (sales, profit and assets) are able to predict competitiveness in this sample. We conclude therefore, in addition to studies on measures of business competitiveness, the combination of indicators that best explains the phenomenon of competitiveness, and that few actors in this sample can change your competitive position in time, reinforcing the Resources Based View (RBV).